2010
DOI: 10.1002/ijc.25629
|View full text |Cite
|
Sign up to set email alerts
|

Differential hypermethylation of genes in vulvar cancer and lichen sclerosus coexisting or not with vulvar cancer

Abstract: Squamous cell carcinoma (SCC) of the vulva is a heterogeneous disease, associated or not with vulvar lichen sclerosus (LS). The precursor role of LS in vulvar cancer is unclear. We studied the epigenetic alterations of RASSF1A, RASSF2A, p16, TSP-1 and MGMT genes in vulvar SCCs, LS associated with SCC, isolated LS and normal vulvar skin. Gene hypermethylation and human papillomavirus presence were evaluated by methylation-specific PCR and PCR/reverse line blot, respectively. High-risk human papillomavirus types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
50
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 46 publications
8
50
4
Order By: Relevance
“…p53 and phosphatase and tensin homolog (PTEN) mutations and microsatellite instability have been demonstrated in early-stage HPV-independent vulvar carcinogenesis [16,23,24,25,26]. In addition, the possible role of Ras-association domain family 2A (RASSF2A), O-6-methylguanine-DNA methyltransferase (MGMT), and thrombospondin-1 (TSP-1) genes in transcriptional silence caused by methylation has been reported [27,28].…”
Section: Vulvar Oncogenesismentioning
confidence: 99%
“…p53 and phosphatase and tensin homolog (PTEN) mutations and microsatellite instability have been demonstrated in early-stage HPV-independent vulvar carcinogenesis [16,23,24,25,26]. In addition, the possible role of Ras-association domain family 2A (RASSF2A), O-6-methylguanine-DNA methyltransferase (MGMT), and thrombospondin-1 (TSP-1) genes in transcriptional silence caused by methylation has been reported [27,28].…”
Section: Vulvar Oncogenesismentioning
confidence: 99%
“…Many TSGs in vulvar cancer, including tumor protein p73 ( TP73 ), immunoglobulin superfamily member 4 ( IGSf4 ), DAPK1, RASSF1A, RASSF2A, CDKN2A , thrombospondin 1 ( TSP-1 ), MGMT , and others, are inactivated through promoter region DNA hypermethylation. Among these genes, TSP-1 shows a potential prognostic role in VSCC recurrence (137), and TP73 displays features that may serve as therapeutic biomarkers in vulvar cancer (138). DNA hypomethylation patterns may also be used as potential prognostic markers in several cancers.…”
Section: Diagnostic and Prognostic Utility Of Epigenetic Alterations mentioning
confidence: 99%
“…However, chronic broadband UVA irradiation of human keratinocytes can induce alterations in histone modification and sever promoter hypermethylation of p16 INK4a , leading to substantial impairment of p16 INK4a transcription. 10 Guerrero et al 8 demonstrated that there was increasing hypermethylation of genes from isolated VLS associated with vulvar SCC. The genes were hypermethylated more frequently in vulvar SCCs associated with LS than in those not associated with LS.…”
Section: Discussionmentioning
confidence: 99%
“…6 Hypermethylation of genes such as TP53, KRAS, CDKN2A (p16) and DAPK1 has been reported in both genital LS and LS-associated SCCs. [7][8][9][10][11][12][13] DNA methylation at the 5-position of cytosine is well recognized as an important epigenetic modification in human health and disease. 10 Recent evidence has demonstrated that 5-methylcytosine (5mC) can be converted by teneleven translocation (TET) enzymes in association with isocitrate dehydrogenases (IDHs) to 5-hydroxymethylcytosine (5hmC).…”
mentioning
confidence: 99%